An integrated approach for mapping fire suppression difficulty in three different ecosystems of Eastern Europe. Issue 1 (2nd January 2017) - Mitsopoulos, I.; Mallinis, G.; Zibtsev, S.; Yavuz, M.; Saglam, B.; Kucuk, O.; Bogomolov, V.; Borsuk, A.; Zaimes, G.
Abstract: Increased fire activity, related both to human activities and to climate change, necessitates effective fire prevention and suppression strategies. The main purpose of this paper is to model and map fire suppression difficulty using common approaches in three different ecosystems in Eastern Europe by employing very high-resolution satellite imagery and landscape fire behaviour modelling. The integrated approach could allow fire managers to organize prevention and management of firefighting activities more efficiently by implementing both simple and easy-to-use risk and operational fire suppression difficulty indices. The development of cross-border common methodological approaches could foster cooperation between national authorities that would also maximize the efficiency of firefighting procedures.